Developing Students' Critical Thinking Abilities about Environmental Change using the Discovery Method of E-Learning - Rufus Olanrewaju Adebisi (Journal of Learning and Educational Policy, 2022)
This research intended to examine how students' critical thinking was affected by exposure to e-learning modules on the topic of environmental change. In this research, we adopted a sequential explanatory design with many techniques of investigation. The indicators adapted from critical thinking abilities by (D'Alessio et al., 2019), (Janssen et al., 2019), and (Koenig et al., 2019) were used in the interviews, observations, and essay tests that provided the data (Sasson et al., 2018). Seventy eighth-graders from a rural middle school took part in the research. Analyses of both quantitative data (mean and standard deviation) and qualitative data (interviews and observations) were conducted. There were three tiers of students' critical thinking abilities, with 15 students (21.91%) scoring in the high range, 40 students (57.83%) scoring in the intermediate range, and 15 students (23.47%) scoring in the low range. An examination of qualitative data revealed that this kind of instruction inspired pupils to seek out information on their own initiative and with great enthusiasm. This research revealed the state of students' critical thinking abilities in middle school, particularly as it relates to the topic of environmental change, where they have lagged behind. Therefore, the use of non-traditional teaching methods to foster critical thinking in pupils is urgently required. More than that, the COVID-19 pandemic provided data on the integration of the discovery learning approach with e-learning in an Islamic school.